Amino Acid Evidence Indicating Two or More Ages of Pre-Holocene Nonglacial Deposits In Hudson Bay Lowland, Northern Ontario - Wyatt, Philip (Géographie physique et Quaternaire, 1990)
ABSTRACTAmino acid studies have identified pre-Holocene non-glacial sediments in the Hudson Lowland which are significantly younger than Bell Sea sediments of the Missinaibi Formation. This younger unit is represented by marine sediments on the Severn and Abitibi rivers. Buried organic material on Beaver River is correlated with the younger Severn and Abitibi river marine sediments based on amino acid evidence. Assuming that Bell Sea sediments are of last interglacial (130-120 ka) age, the younger nonglacial sediments may have been deposited late in 18O stage 5 (80-75 ka). Paleoecologic studies of the Beaver River organics indicate climate at least as warm as present.